Validitas tes tertulis pada model pembelajaran blended learning mata pelajaran IPA di SD - Aliani, Gazella Fitri (ARKA INSTITUTE, 2022)
The written test is a collection of questions given to students to test the level of students' knowledge of the material presented. Subjects that are suitable for written tests are science. Before the written test is held, you must use a learning model that is in accordance with the Covid-19 situation in Indonesia, namely using the Blended Learning model. To ensure the quality of the written test, a special study is needed to assess the validity. This study aims to assess aspects of the validity of the written test. This research is a descriptive quantitative research that presents the data from the validation results and the validator's suggestions on the validity of the written test. The validator consists of two people, namely a lecturer at PGRI Adi Buana University and the other a fifth grade teacher at elementary school of Pepelegi II Waru. The instrument used is a written test sheet. The results of the analysis of the validation sheet show that in general the written test meets the valid criteria.